Finance and Development, December 1984. (Finance and Development; Finance and Development ;, 1984)
This paper reviews the increasing private capital flows to less developed countries. The share of developing countries in the foreign direct investment is small, perhaps less than 30 percent of the total. The effects of this decline in the volume of foreign investment and the continued problem of capital flight have been aggravated by the serious fall in commercial bank lending to developing countries as a group and by a decline in official development assistance.